Potential key genes involved in metabolic resistance to malathion in the southern house mosquito, Culex quinquefasciatus, and functional validation of CYP325BC1 and CYP9M12 as candidate genes using RNA interference - Xinyue Huang; Phillip E. Kaufman; Giridhar N. Athrey; Chris Fredregill; Christina Alvarez; Vinaya Shetty; Michel A. Slotman (BMC Genomics, 2023)
Abstract Background Metabolic detoxification is one of the major mechanisms contributing to the development of resistance in mosquitoes, including the southern house mosquito, Culex quinquefasciatus. The three major detoxification supergene families, cytochrome P450s, glutathione S-transferases and general esterases, have been demonstrated to play an important role in metabolic resistance. In this study, we performed differential gene expression analysis based on high-throughput transcriptome sequencing on samples from four experimental groups to give insight into key genes involved in metabolic resistance to malathion in Cx. quinquefasciatus. We conducted a whole transcriptome analysis of field captured wild Cx. quinquefasciatus from Harris County (WI), Texas and a malathion susceptible laboratory-maintained Sebring colony (CO) to investigate metabolic insecticide resistance. Field captured mosquitoes were also phenotypically classified into the malathion resistant and malathion susceptible groups following a mortality response measure conducted using a Centers for Disease Control and Prevention (CDC) bottle assay. The live (MR) and dead (MS) specimens from the bottle assay, along with an unselected WI sample and a CO sample were processed for total RNA extraction and subjected to whole-transcriptome sequencing. Results We demonstrated that the genes coding for detoxification enzymes, particularly cytochrome P450s, were highly up-regulated in the MR group compared to the MS group with similar up-regulation observed in the WI group compared to the CO group. A total of 1,438 genes were differentially expressed in comparison between MR and MS group, including 614 up-regulated genes and 824 down-regulated genes. Additionally, 1,871 genes were differentially expressed in comparison between WI and CO group, including 1,083 up-regulated genes and 788 down-regulated genes. Further analysis on differentially expressed genes from three major detoxification supergene families in both comparisons resulted in 16 detoxification genes as candidates potentially associated with metabolic resistance to malathion. Knockdown of CYP325BC1 and CYP9M12 using RNA interference on the laboratory-maintained Sebring strain significantly increased the mortality of Cx. quinquefasciatus after exposure to malathion. Conclusion We generated substantial transcriptomic evidence on metabolic detoxification of malathion in Cx. quinquefasciatus. We also validated the functional roles of two candidate P450 genes identified through DGE analysis. Our results are the first to demonstrate that knockdown of CYP325BC1 and CYP9M12 both significantly increased malathion susceptibility in Cx. quinquefasciatus, indicating involvement of these two genes in metabolic resistance to malathion.